2019
DOI: 10.1200/po.18.00162
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Tumor-Specific Mutated and Methylated DNA in Colorectal Cancer

Abstract: PURPOSE Analysis of circulating tumor DNA (ctDNA) is a potential improvement in precision medicine. In colorectal cancer (CRC), somatic mutations such as RAS and RAF in the blood (mut-ctDNA) are investigated for prognostic and predictive purposes. However, they are only present in approximately 60% of patients. Recently, ctDNA has been detected in patients with RAS/ RAF wild type (WT) by methylated ctDNA (meth-ctDNA). The aim of this study was to compare mutated DNA with methylated DNA in malignant and nonmali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In this study, NPY was discarded due to positivity in normal mucosa and in whole blood samples (which contain white blood cells as the main contaminant of cfDNA), and WIF1 was found to have limited differential methylation between normal healthy/normal adjacent mucosa and tumor. Other recently published studies found NPY methylation in the plasma of healthy donors (14) and non-cancer patients (15). Therefore, to date, we are far from true agreement on the use of WIF-1/NPY methylation testing to exclude or confirm the presence of ctDNA.…”
Section: Clearance Of Ras Mutation In Plasma: Methylation To Confirm/mentioning
confidence: 76%
“…In this study, NPY was discarded due to positivity in normal mucosa and in whole blood samples (which contain white blood cells as the main contaminant of cfDNA), and WIF1 was found to have limited differential methylation between normal healthy/normal adjacent mucosa and tumor. Other recently published studies found NPY methylation in the plasma of healthy donors (14) and non-cancer patients (15). Therefore, to date, we are far from true agreement on the use of WIF-1/NPY methylation testing to exclude or confirm the presence of ctDNA.…”
Section: Clearance Of Ras Mutation In Plasma: Methylation To Confirm/mentioning
confidence: 76%
“…Meth-ctDNA has already been suggested as a universal cancer-specific biomarker in previous studies [ 14 , 17 , 31 ]. The present study finds that meth-HOXA9 is a sensitive and specific biomarker of advanced lung adenocarcinoma in tumor tissue, and it has promising qualities for use in liquid biopsies.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA was extracted from formalin-fixed, paraffin-embedded (FFPE) lung tissue (tumor or non-tumor), as previously described [ 31 ]. In tumor tissue, areas with a high degree of tumor cells were selected by an experienced pathologist.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations